1993
DOI: 10.1084/jem.177.4.1031
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor beta 1 selectivity stimulates immunoglobulin G2b secretion by lipopolysaccharide-activated murine B cells.

Abstract: Bacterial lipopolysaccharide (LPS) has been reported to induce immunoglobulin (Ig)G2b class switching, yet we observed strain differences in IgG2b secretion in response to this mitogen. Specifically, BALB/c B cells, unlike those from DBA/2, synthesized relatively low amounts of IgG2b relative to IgG3, IgG1, or IgM. This report demonstrates that transforming growth factor (TGF) beta 1, previously shown to induce IgA class switching, selectively stimulates IgG2b secretion by BALB/c resting B cells activated with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
83
2
1

Year Published

1994
1994
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 152 publications
(97 citation statements)
references
References 36 publications
11
83
2
1
Order By: Relevance
“…No other cytokine was correlated with IgG2bIF. As IgG2bIF is not yet fully characterized, there have been suggestions that it might be identical to other cytokines, such as TGF-b [24]. However, here we show that IgG2bIF is not closely correlated with any other cytokine in the SF samples, which rules out identity with any of the cytokines included in this study.…”
Section: Presence Of Igg2bif Correlates With High Levels Of Il-10 Andcontrasting
confidence: 75%
See 1 more Smart Citation
“…No other cytokine was correlated with IgG2bIF. As IgG2bIF is not yet fully characterized, there have been suggestions that it might be identical to other cytokines, such as TGF-b [24]. However, here we show that IgG2bIF is not closely correlated with any other cytokine in the SF samples, which rules out identity with any of the cytokines included in this study.…”
Section: Presence Of Igg2bif Correlates With High Levels Of Il-10 Andcontrasting
confidence: 75%
“…TGF-b may be important in cartilage repair, as it can induce collagen synthesis [39]. At lower concentrations, TGF-b is a switch factor for immunoglobulin A (IgA) production [40][41][42] and it is necessary for production of all IgG subclasses in murine B cells [43] and for the induction of IgG2b production [24,31]. As high RF titres are a characteristic feature of RA, a potential pathogenic role for TGF-b might be to locally stimulate antibody production.…”
Section: Discussionmentioning
confidence: 99%
“…Ig isotype switching is a critical event in B-cell differentiation, and TGF-β1 is a specific switching factor for the IgA and IgG2b mouse isotype (Kim and Kagnoff, 1990;McIntyre et al, 1993). Since we have previously demonstrated that TGF-β1 stimulates mouse macrophages to express BAFF (Kim et al, 2008), it was worthwhile to investigate if TGF-β1 can modulate macrophages to express another member of the same family, APRIL.…”
Section: Resultsmentioning
confidence: 99%
“…Purified naive B cells were activated with 10 mg/ml anti-mouse IgM F(ab9) 2 Ab with DCs from MLN of control or VAD mice. Recombinant mouse IL-5 (10 ng/ml; R&D Systems, Minneapolis, MN), ATRA (100 nM; Sigma-Aldrich), and RA antagonist LE540 (100 nM; Wako, Japan) were used in an in vitro culture system.…”
Section: B Cell Activation In Vitromentioning
confidence: 99%